Editorial - (a cura di) Massimiliano Demata; (a cura di) Dermot Heaney; (a cura di) Susan C. Herring (Altre Modernità, 2018)
Language and Discourse in Social Media: New Challenges, New Approaches. by Massimiliano Demata, Dermot Heaney and Susan C. Herring